Risk Factors Associated with Pyogenic Spinal Infections among Intravenous Drug Users and Nonusers - Vivek K. Bilolikar; Brendan Gleason; Lee Kripke; Robert Merrill; Colin Whitaker; Jon Handal (Advances in Orthopedics)
Background Data. Spinal infections are major clinical problems with a substantial financial burden on healthcare systems. Recent increases in primary pyogenic spine infections can be attributed to the opioid epidemic and an aging and increasingly unhealthy population. Immunocompromise, diabetes, and malignancy all predispose patients to spine infections. Purpose. To identify the differences in patient factors, presentation, treatment course, and outcomes of intravenous drug users (IVDA) vs. nonusers (non-IVDA) presenting with pyogenic spinal infections. Study Design/Setting. Retrospective case series. Methods. We identified all cases involving spinal infections at our institution between May 2017 and January 2023. Postsurgical infections were excluded, and patients were separated into IVDA and non-IVDA groups. The patient charts were reviewed and analyzed for statistical or clinically significant differences using RStudio (2019 version 3.6.2). Our institutional review board approved this study, IRB# 2020-277, iRISID-2023-1384. Results. Fifty patients (29 males and 21 females) with primary pyogenic spinal infections were included in our study. There were fourteen patients (28.0%) in the IVDA group. The mean age in the IVDA group was 50.6 vs. 61.9 years (p<0.05) in the non-IVDA group. The average length of stay (LOS) in the IVDA group was 15.8 vs. 14.0 days (p=0.54) in the non-IVDA group, with no significant difference in readmissions or disposition. Twenty-three non-IVDA patients were diagnosed with diabetes, while eight IVDA patients had a psychiatric diagnosis (other than substance abuse). There were no significant differences in microbial isolate or the duration of antibiotics. Conclusion. In our study population, there is a high incidence of intravenous drug abuse (IVDA), psychiatric disease, diabetes, and chronic kidney disease. Analysis shows a trend of two distinct patient populations. Patients without a history of IVDA were significantly older than those with IVDA and significantly more likely to have medical comorbidities including hyperlipidemia, diabetes, chronic kidney disease, and malignancy than those with IVDA history. Patients with IVDA were younger with significantly higher rates of smoking and psychiatric disorders. IVDA patients struggled to receive continued psychiatric/addiction treatment after discharge, an area for significant improvement. Due to a small sample size and single urban institution setting, this study may be underpowered to demonstrate differences in healthcare resource consumption.